Old versus new in the Sa'udi expansions of the mosque of the Prophet (S.A.W) - Omer, Spahic (Hamdard Foundation, 2018)
This paper discusses the relationship between tradition and modernity in the Saudi expansions of the Prophet’s Mosque. Two major expansions by King ‘Abd al-‘Aziz and King Fahd have been targeted. The first expansion by the first Saudi King, during the Kingdom’s formative years, is regarded as a precursor to the second one, which was truly epic and grandest of all previous expansions. The latter was necessitated by the factors of incessant overcrowding and King Fahd’s need for boosting an Islamic image. When completed, the Mosque represented a harmonious blend between old and new, and between tradition and modernity. It was modern and progressive in terms of its form, structural performance and engineering means and methods, but traditional and conventional in terms of its embedded meaning, function and substance. The Mosque oozed the aura of authentic Islamic architecture.